1997
DOI: 10.1046/j.1471-4159.1997.69051882.x
|View full text |Cite
|
Sign up to set email alerts
|

Disrupted [Ca2+]i Homeostasis Contributes to the Toxicity of Nitric Oxide in Cultured Hippocampal Neurons

Abstract: Nitric oxide (NO) has been shown to be an important mediator in several forms of neurotoxicity. We previously reported that NO alters intracellular Ca2+ concentration ([Ca2+]i) homeostasis in cultured hippocampal neurons during 20‐min exposures. In this study, we examine the relationship between late alterations of [Ca2+]i homeostasis and the delayed toxicity produced by NO. The NO‐releasing agent S‐nitrosocysteine (SNOC; 300 µM) reduced survival by about one half 1 day after 20‐min exposures, as did other NO‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…NO acts at the level of cytochrome oxidase, reducing the affinity of the enzyme for O 2 (12,16). Disruption of mitochondrial respiration by NO has been proposed to be partially responsible for the energy depletion in neurons (10) that led to the disruption of Ca 2ϩ homeostasis (11). We have demonstrated previously that in vascular endothelial cells, NO inhibits capacitative Ca 2ϩ entry and enhances endoplasmic reticulum Ca 2ϩ uptake; however, the effect of NO on mitochondrial Ca 2ϩ homeostasis has not been evaluated in details (19).…”
Section: Discussionmentioning
confidence: 99%
“…NO acts at the level of cytochrome oxidase, reducing the affinity of the enzyme for O 2 (12,16). Disruption of mitochondrial respiration by NO has been proposed to be partially responsible for the energy depletion in neurons (10) that led to the disruption of Ca 2ϩ homeostasis (11). We have demonstrated previously that in vascular endothelial cells, NO inhibits capacitative Ca 2ϩ entry and enhances endoplasmic reticulum Ca 2ϩ uptake; however, the effect of NO on mitochondrial Ca 2ϩ homeostasis has not been evaluated in details (19).…”
Section: Discussionmentioning
confidence: 99%
“…In neurons, NO administered exogenously (Brorson and Zhang 1997; Brorson et al . 1997) or generated endogenously after NMDA receptor stimulation (Marks et al .…”
Section: Signalling Roles Of the No‐cytochrome C Oxidase Pathwaymentioning
confidence: 99%
“…Application of SNAP or SNP did not disrupt Ca 2ϩ homeostasis in N20.1 cells within our time of observation (up to 15 min). NO induces a rise in intracellular Ca 2ϩ concentration in several cell types, including hepatocytes, the murine macrophage cell line PU5-1.8, pancreatic islet cells, hippocampal neurons, and oligodendrocytes (Hartmann et al, 1994;Kong et al, 1994;Richter et al, 1994;Brorson and Zhang, 1997;Nedelkoska et al, 1997). These studies showed that the origin of the increased intracellular Ca 2ϩ level may be extracellular, intracellular, or sometimes both.…”
Section: Figmentioning
confidence: 99%